Governing rapid growth in China: Equity and institutions - Kanbur, Ravi; Zhang, Xiaobo (Routledge, 2009)
After three decades of spectacular economic growth in China, the problem is no longer how to achieve growth, but how to manage its consequences and how to sustain it. The most important consequence, at least as far as Chinese policy makers are concerned, is the rapidly growing inequality, between persons, between rural and urban areas, and between inland and coastal regions. At the same time, the institutions that have brought rapid growth so far are now under stress, and there is a need to reform and innovate on this front in order to sustain rapid growth, and to have growth with equity.